Data-Focused Approach: Developing A New Intervention Method In Applied Psychology - Johana E Prawitasari; Tiara R. Widiastuti; Walida Asitasari (Jurnal Psikologi, 2019)
This study aims to compare the newly developed psychological intervention method by the first author, named data-focused approach, to the more classical process-oriented approaches, i.e. gestalt, psychodynamics, and interactional group psychotherapies. Pretest-posttest design was used. Twenty-one participants were assigned into four experimental groups. Measures used were self-regulation, emotional awareness, and meta-emotion scales as well as stated agenda on interpersonal relationship. They were administered before and after therapy sessions. Results indicated that the new method evidently was compatible to the classical psychotherapy approaches. Specifically, participants in the data-focused approach were satisfied with the aiming behavioral change in their interpersonal relationship. The new approach is effective to be applied in the group processes. Thus, this new method is also recommended to be studied in other settings. Using simplified procedure, it is hoped that other professionals, like medical doctor, nurse, midwife, women activists in public health centers may use it to serve better the community.